From Chalkboards to Cyberspace: The Role of Augmented and Virtual Reality in Transforming Mathematics Education - Brindha Devi Sairam; Radhakrishnan Ramnath (Journal of Computers for Science and Mathematics Learning, 2026)
The integration of immersive technologies, such as Augmented Reality (AR) and Virtual Reality (VR), is reshaping educational landscapes, particularly in mathematics instruction. These tools provide dynamic visualizations and interactive simulations that bridge the gap between abstract theories and experiential learning. This narrative review explores the evolving role of AR and VR in mathematics education, emphasizing their application in understanding three-dimensional (3D) geometric concepts. The review seeks to address two main questions: (a) How are AR and VR technologies applied in the teaching of mathematics? (b) To what extent do immersive learning environments enhance students’ understanding and achievement in 3D geometry? Recent research indicates that AR and VR contribute to improved conceptual understanding, increased engagement, and enhanced spatial visualization by enabling learners to interact with mathematical objects in realistic and immersive settings. These technologies promote active learning and the development of higher-order thinking skills, while motivating students through experiential engagement. The review finds that AR and VR possess significant transformative potential for mathematics education, offering innovative pathways for conceptual growth and cognitive involvement. To fully realize this potential, future research should prioritize scalable implementation strategies, comprehensive teacher training, and an assessment of the long-term pedagogical impact of immersive technologies within classroom settings.